MĪRĀTH ALMTḤWL JNSYAN DIRĀSAH FIQHĪYAH QĀNŪNĪYAH - Hammad, Hamza Abed Alkarim (Islam Futura, 2024)
The aim of this study is discussing the contemporary Fiqh views on the impact of sex change on transgender inheritance and discuss them. The study followed the comparative critical inductive approach. The study ended up dividing the impact of sex change on transgender inheritance into two forms; the first: if the transgender is the inheritor, then his share is the share of the hermaphrodite formed according to the Hanafi school; to activate the principle of Ta'zir by taking money, and the position of Hanafi is necessary for the Jordanian Personal Status Law. If the transferee is the inheritor, there is no effect of the transferee on the share of the heirs.